Protective effects of recombinant human bone morphogenetic protein-7 on focal cerebral ischemia–reperfusion injury. (19th April 2013) - Xu, Ji-Hong; Zhang, Tie-Zheng; Zhao, Yan-Yan; Wang, Jun-Ke; Yuan, Zhi-Guo
<x xml:space="preserve">Abstract</x> This study was to investigate the protective effect of recombinant human bone morphogenetic protein-7 (rhBMP-7) on focal cerebral ischemia–reperfusion (IR) injuries and their underlying mechanisms. An intraluminal suture method was used to generate a middle cerebral artery occlusion model in rats, which was followed by reperfusion. A sham operation (SO) group underwent the procedure without occlusion, whereas an IR group and rhBMP-7 treated group (RT) underwent occlusion in the absence and presence of rhBMP-7 (250 μg/kg) administered via a femoral vein injection 30 minutes prior to reperfusion. Twenty-four hours after reperfusion, neurological function, brain water content and morphological alterations were examined. Apoptosis was detected using terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling assays, and immunohistochemical staining and Western blot assays were used to detect nuclear nuclear factor-kappa B (NF-κB) p65 expression. Compared with the SO group, IR rats showed a decrease in neurological function, an increase in brain water content, and pathological and morphological damage (p < 0.05). Higher levels of apoptosis were also detected in the infarct region area. In contrast, RT rats had reduced injury after IR. In addition, while immunohistochemical staining and western blot assays consistently detected increased expression of nuclear NF-κB after IR, these levels were reduced in the RT group. Administration of rhBMP-7 prior to reperfusion effectively inhibited the extent of IR injury by attenuating cerebral edema and ameliorating ultrastructural damage. The underlying mechanisms responsible for these observations potentially involve the inhibition of apoptosis induced by IR by rhBMP-7 via an NF-κB-related signaling cascade.